A modified secure hash design to circumvent collision and length extension attacks. (December 2022) - Al-Odat, Zeyad A.; Khan, Samee U.; Al-Qtiemat, Eman
Abstract: This paper introduces an improved version of the secure hash algorithms, SHA-1, and SHA-2. The proposed work produces a strengthened secure hash design using the fusion between the SHA-1 and SHA-2 hash standards. This design helps to protect the SHA-1 and SHA-2 against collision and length extension attacks. The proposed design is incorporated in the round steps of the hash functions using the function manipulators of the SHA-1 and SHA-2. Moreover, the proposed design employs a padding method that is different from the one used in the SHA-1 and SHA-2 construction. The proposed design is verified by the official test vectors that were confirmed by the National Institute of Standard and Technology. Moreover, the avalanche effect, hamming distance, and bit-hit properties were studied using different test cases. The proposed design gives over 52 percent of the avalanche effect and over 84 hamming distance. The proposed design was tested against collision attack and produced unique hash values for real collided examples and shows resistance against length extension attack.